D-Serine and Serine Racemase Are Associated with PSD-95 and Glutamatergic Synapse Stability - Lin, Hong; Jacobi, Ariel A.; Anderson, Stewart A.; Lynch, David R. (Frontiers in Cellular Neuroscience, 2016)
D-serine is an endogenous coagonist at the glycine site of synaptic NMDA receptors (NMDARs), synthesized by serine racemase (SR) through conversion of L-serine. It is crucial for synaptic plasticity and is implicated in schizophrenia. Our previous studies demonstrated specific loss of SR, D-serine-responsive synaptic NMDARs, and glutamatergic synapses in cortical neurons lacking alpha7 nicotinic acetylcholine receptors, which promotes glutamatergic synapse formation and maturation during development. We thus hypothesize that D-serine and SR (D-serine/SR) are associated with glutamatergic synaptic development. Using morphological and molecular studies in cortical neuronal cultures, we demonstrate that D-serine/SR are associated with PSD-95 and NMDARs in postsynaptic neurons and with glutamatergic synapse stability during synaptic development. Endogenous D-serine and SR colocalize with PSD-95, but not presynaptic vesicular glutamate transporter 1 (VGLUT1), in glutamatergic synapses of cultured cortical neurons. Low-density astrocytes in cortical neuronal cultures lack SR expression but contain enriched D-serine in large vesicle-like structures, suggesting possible synthesis of D-serine in postsynaptic neurons and storage in astrocytes. More interestingly, endogenous D-serine and SR colocalize with PSD-95 in the postsynaptic terminals of glutamatergic synapses during early and late synaptic development, implicating involvement of D-serine/SR in glutamatergic synaptic development. Exogenous application of D-serine enhances the interactions of SR with PSD-95 and NR1, and increases the number of VGLUT1- and PSD-95-positive glutamatergic synapses, suggesting that exogenous D-serine enhances postsynaptic SR/PSD-95 signaling and stabilizes glutamatergic synapses during cortical synaptic development. This is blocked by NMDAR antagonist 2-amino-5-phosphonopentanoic acid (AP5) and 7-chlorokynurenic acid (7-CK), a specific antagonist at the glycine site of NMDARs, demonstrating that D-serine effects are mediated through postsynaptic NMDARs. Conversely, exogenous application of glycine has no such effects, suggesting D-serine, rather than glycine, modulates postsynaptic events. Taken together, our findings demonstrate that D-serine/SR are associated with PSD-95 and NMDARs in postsynaptic neurons and with glutamatergic synapse stability during synaptic development, implicating D-serine/SR as regulators of cortical synaptic and circuit development.